Newly qualified chiropractors' perceptions of preparedness for practice: A cross-sectional study of graduates from European training programs. - Pulkkinen, Elina; de la Ossa, Pablo Pérez (Journal of Chiropractic Education (Allen Press Publishing Services Inc.), 2019)
Objective: The purpose of this pilot study was to explore chiropractic graduates' perceived preparedness for practice in the 7 key competencies of the Canadian Medical Education Directives for Specialists. Methods: An anonymous 5-point Likert scale electronic questionnaire was distributed to graduates from the 2014-2016 cohorts of 9 European chiropractic colleges accredited by the European Council of Chiropractic Education. For each group under 1 competency role, the mean overall score was calculated. Statistical differences were analyzed using at test and analysis of variance. Cronbach's alpha was calculated for internal consistency. Results: Results of 7 chiropractic colleges were analyzed (n = 121). Differences were found among colleges, competencies, and items. Overall, the graduates who responded scored the lowest in collaborator (3.76) and scholar (3.78) competencies. They scored the highest in professional (4.39) and chiropractic expert (4.13) competencies. In all colleges, a lower level of perceived preparedness was found in collaborator, scholar, and manager competencies. Statistical differences were found that compared the type of employment and cohorts. Conclusion: Our results show there may be a gap between education and professional practice regarding perceived preparedness, and graduates perceived themselves to be unprepared in some competencies. The preliminary results of this study could be used to improve curricula of chiropractic education.